1993
DOI: 10.1111/j.1471-4159.1993.tb03498.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neurite Outgrowth Induced by Inhibition of Protein Tyrosine Kinase Activity in PC12 Pheochromocytoma Cells

Abstract: Genistein and other inhibitors of protein tyrosine kinases were examined for effects on neurite elongation and growth cone morphology in the rat PC12 pheochromocytoma cell line. Genistein increased the rate of neurite elongation in PC12 cells grown on a collagen/polylysine substratum after priming with nerve growth factor (NGF), but had no effect on undifferentiated cells. Steady-state levels of phosphotyrosine-modified proteins (105, 59, 52, and 46 kDa) were reduced in NGF-primed cells by genistein treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 56 publications
6
42
0
Order By: Relevance
“…Our data show that the nonreceptor PTK pp60 c-src that is concentrated in nerve growth cones of developing and regenerating neurons (Maness et al, 1988;Ignelzi et al 1992) can be activated through activation of extracellularly applied bradykinin. Inhibition of pp60 c-src present in PC12 growth cones (Miller et al, 1993) by genistein is also in good agreement with our results. Therefore, the pp60 c-src may be involved in bradykinininduced growth cone collapse.…”
Section: Discussionsupporting
confidence: 92%
“…Our data show that the nonreceptor PTK pp60 c-src that is concentrated in nerve growth cones of developing and regenerating neurons (Maness et al, 1988;Ignelzi et al 1992) can be activated through activation of extracellularly applied bradykinin. Inhibition of pp60 c-src present in PC12 growth cones (Miller et al, 1993) by genistein is also in good agreement with our results. Therefore, the pp60 c-src may be involved in bradykinininduced growth cone collapse.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been shown to affect a number of cell surface parameters, leading to reductions in cell adhesion (42) growth factor, and insulin receptor families (26). cells on collagen (27 Studies by over-expression of v-Src and by inhibitors of its family have indicated that Src family may function during the neural cell differentiation, axonal guidance, and synaptic transduction. The mutation analyses in Drosophila have shown that the mutation of D-Src or Abelson (Abl) tyrosine kinase has not disturbed the neural formation, but the double null mutant of Abl and fasciclin I exhibits aberrant growth cone navigation and abnormal neural networks (13).…”
Section: Functional Analyses For Src Family Kinasesmentioning
confidence: 99%
“…It also inhibits microsomal lipid peroxidation [12] and angiogenesis [13] . Genistein exhibits antioxidant properties [14][15][16] and was reported to induce differentiation of numerous cell types [17][18][19] . Moreover, a recent report shows that genistein is a potent cancer chemopreventive agent [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%